ANALISIS PERAN ADVOKASI ORGANISASI MAJLIS UGAMA ISLAM SINGAPURA TERHADAP UMAT MUSLIM DI NEGARA MULTIKULTURAL SINGAPURA - Putri, Riske Mutia; Putri, Made Caroline Cleo Dwi Indira; Mas, Ratu Ayu Allysia Luna Sita Manik (Magister Administrasi Publik FISIP Universitas Mulawarman, 2024)
This research examines a religion-based organization in one of the Southeast Asian countries, Singapore, named Majlis Ugama Islam Singapura (MUIS). The purpose of establishing MUIS is to accommodate and channel the aspirations of the Muslim community in Singapore in carrying out a life based on Islamic values related to their teachings and government. MUIS is engaged in various fields, one of which is the field of advocacy. Advocacy is an activity with the aim of changing policies through processes such as recommendations and requests to achieve solutions to the issues at issue. The purpose of this research is to analyze the advocacy role of MUIS towards Muslims in the multicultural country of Singapore. The research method used is qualitative research through literature analysis or literature study, the results of which are described descriptively. The results of the research answer the role of MUIS in the field of advocacy through providing advice to the President of Singapore regarding issues of Muslim religion in Singapore, harmonizing Islamic religious teachings in accordance with Singaporean laws, advocating in the fields of development and education, and implementing advocacy related to legal products or fatwas.